Breakdown properties of thermoplastic polypropylene and linear low density polyethylene blends - Tiong, Nathanael Yong Sing (2020)
Polymers have always been used as insulators in high voltage industry. Polyethylene and polypropylene are widely used due to their suitability of mechanical and electrical properties to be used as insulators. The purpose of this study was to investigate the breakdown properties of polypropylene and linear low density polyethylene blends. In this project, five different compositions of thermoplastic polymer blends composed of polypropylene (PP) and linear low density polyethylene (LLDPE) were formulated through melt blending method. The breakdown strength of polymer blends with the composition of 100% PP, 80% PP and 20% LLDPE, 50% PP and 50% LLDPE, 20% PP and 80% LLDPE and 100% LLDPE was investigated and analyzed. The results obtained were analysed using Weibull software. The results indicated that the use of appropriate PP and LLDPE blends had enhance their breakdown performances. These improvements showed the potential of the blends to be used as power cable insulators.